2009
DOI: 10.1248/bpb.32.259
|View full text |Cite
|
Sign up to set email alerts
|

Anti-angiogenic and Anti-metastatic Effects of .BETA.-1,3-D-Glucan Purified from Hanabiratake, Sparassis crispa

Abstract: Sparassis crispa (SC), Hanabiratake in Japanese, is an edible mushroom with medicinal properties, which has recently become cultivable in Japan. We have already demonstrated the antitumor and antiallergic activities of this mushroom. 1)SC contains more than 40% of b-D-glucan and it has been reported that its major structural unit are b-(1→3)-D-glucan backbone with single b-(1→6)-D-glucosyl side branching units every three residues.1-3) However, a detailed structure study of b-D-glucan from SC has not been achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 29 publications
0
43
0
3
Order By: Relevance
“…β-1,3-D-glucan of SC is reported to act as an antitumor agent in tumor-bearing mice when injected intraperitoneally. [13] Recent studies have revealed that the levels of serum IL-2 and TNF-in Renal cancer-bearing mice were significantly increased by P. eryngii polysaccharide treatment. The increase of IL-2 and TNF-also explain the antitumorigenic properties of P. eryngii polysaccharide.…”
Section: Figure 2(a): Ft-ir Analysis For Extracted P Eryngii β-Glucanmentioning
confidence: 99%
See 1 more Smart Citation
“…β-1,3-D-glucan of SC is reported to act as an antitumor agent in tumor-bearing mice when injected intraperitoneally. [13] Recent studies have revealed that the levels of serum IL-2 and TNF-in Renal cancer-bearing mice were significantly increased by P. eryngii polysaccharide treatment. The increase of IL-2 and TNF-also explain the antitumorigenic properties of P. eryngii polysaccharide.…”
Section: Figure 2(a): Ft-ir Analysis For Extracted P Eryngii β-Glucanmentioning
confidence: 99%
“…[9] Besides to the immunological effects of β-glucan, many studies proved that β-glucan stimulates phagocytic activity as well as synthesis and release of interleukin-1(IL-1), IL-2, IL-4, IL-6, IL-8, IL-13, and tumor necrosis factor-alpha, [10] inhibitory effects on the growth of tumor cells in vivo and affects expression of several important genes in tumor cells, [11] cell cycle arrest and induction of apoptosis can be seen, [12] activated complement receptors on natural killer cells, neutrophils, and lymphocytes may also be associated with the detected tumor cytotoxicity, [8] and finally anti-angiogenic properties. [13] Angiogenesis is a dynamic process of endothelial proliferation and differentiation. Tumors with high angiogenic activity have been correlated with poor patient survival.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained from headspace analysis indicate that 3-octanone, DL-3-octanol, and 1-octen-3-ol contribute to the particular aroma of this mushroom [4]. Medicinal properties in S. crispa include anticancer activities‚ antiangiogenic‚ anti-metastatic, wound healing and immune stimulation effects [5]- [7]. It has been recorded that β-glucan content of S. crispa is about 43.6% as measured by enzyme method by Japan Food research laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Сучасні відомості щодо лікувальних властивостей S. crispa свідчать про широкий біологічний спектр дії цього гриба (Tada et al, 2007;Dalonso et al, 2015). Встановлено, що екстракти, отримані як з плодових тіл, так і міцеліальної маси даного виду, мають імуномодулюючий, онкостатичний і антиметастатичний ефекти (Woodward et al, 1993;Kwon et al, 2009;Yamamoto et al, 2009;Yoshikawa et al, 2010;Takashi, 2013). За умов глибинного і поверхневого культивування штами S. crispa здатні до біосинтезу антибіотиків і цитокінінів (Dyakov et al, 2011;Vedenicheva et al, 2016).…”
unclassified